2009
DOI: 10.1111/j.1758-0854.2009.01016.x
|View full text |Cite
|
Sign up to set email alerts
|

Managers' Active Support when Implementing Teams: The Impact on Employee Well‐Being

Abstract: Research has shown that a variety of organisational change interventions can be effective but the powerful positive results of an intervention do not always generalise to other similar settings. Problems with implementation and a difficult intervention context have been shown to undermine the effectiveness of promising interventions. The impact that middle managers have on the change process and intervention outcomes has not been widely researched. This longitudinal intervention study was carried out in the el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 33 publications
2
48
1
Order By: Relevance
“…In one of the few studies to examine directly problems in team implementation, Parker and Williams (2001) found that one of the main barriers for effective teams was associated with managerial behaviours (a nonparticipatory leadership style and a lack of detailed feedback on performance). More recently, the importance of managers as drivers of change was confirmed in a study by Nielsen and Randall (2009). Here it was found that the active support for team implementation by middle managers mediated intervention outcomes.…”
Section: Training Managers During Team Implementationsupporting
confidence: 56%
“…In one of the few studies to examine directly problems in team implementation, Parker and Williams (2001) found that one of the main barriers for effective teams was associated with managerial behaviours (a nonparticipatory leadership style and a lack of detailed feedback on performance). More recently, the importance of managers as drivers of change was confirmed in a study by Nielsen and Randall (2009). Here it was found that the active support for team implementation by middle managers mediated intervention outcomes.…”
Section: Training Managers During Team Implementationsupporting
confidence: 56%
“…It has been argued that the intervention process and the behaviours of key players, such as line managers, have a What works for whom? prominent role in supporting the intervention and shaping its outcomes (Nielsen and Abildgaard, 2013;Nielsen and Randall, 2009). Also the participatory process, i.e.…”
Section: Challenges To Internal Validitymentioning
confidence: 99%
“…The theme consisting of just one manager, who did not seem to be able to use the intervention at all, was not shared by the consultants. The reason for that is unclear but it once again suggests the manager's importance in distributing a change process [9][10][11]21]. Why the managers' theme of becoming a team were not a shared experience with the consultants raises questions, especially since this was the purpose of the intervention [1].…”
Section: Discussionmentioning
confidence: 99%
“…This theme was captured among the managers with groups that retrograde development. It seems that the managers and their attitudes towards the intervention remains of immense importance [3,9,10,[19][20][21] and since the narratives of their leadership were exclusive for the 'retrograde' managers and not shared by the consultants its appealing to interpret the statements as either a way of defending themselves against shameful associations [12] in that they were afraid of implementing the change [19], or as an expression of resentfulness that their specific needs were not being met [16]. The second experience, this time by the managers that showed progress, not shared with the consultants was statements about that they had wanted the fitters to have been involved in the workshops.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation